Common Science Misconceptions among Junior, Secondary School, and College Freshmen: A Case Study in Dire Dawa City, Ethiopia - Goshu, Belay Sitotaw; Misganu, Tewodros; Abas, Ermias; Woldeamanue, Melaku Masresha; Ridwan, Muhammad (BIRCU, 2024)
The aim of this study was to clarify misconceptions about science subjects among middle school, high school, and first-year university students in Dire Dawa City. The sample size was 1,576 first-year middle school and university students in Dire Dawa, Ethiopia. The researchers asked each participant to write responses to open-ended questions about general concepts in biology, chemistry, and physics. The authors use descriptive analysis techniques. These results show that 31.6% of respondents and 49.9% of respondents incorrectly believe that breathing, breathing, and germs are always incorrect concepts. Furthermore, it was found that 33.0% of respondents had a misunderstanding that